2021
DOI: 10.22454/primer.2021.249084
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of American Medical Students’ Knowledge of Physical Activity Recommendations

Abstract: Introduction: The benefits of physical activity (PA) are widely recognized; American medical schools have begun to emphasize PA, but the effectiveness of these changes is unclear. Methods: We performed a cross-sectional analysis of medical students enrolled in US osteopathic and allopathic medical schools between August 2019 and May 2020. All participants completed an electronic survey about PA instruction across the 4 years of medical school. Objective information including hours and format of PA instruction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Therefore, one of the reasons for the low involvement of antenatal physicians in the promotion of physical activity may be their insufficient education in this area during their studies and gynaecological specialization. Now that new, modern recommendations in this area have also been published in Poland ( 13 ), this important aspect of education and health promotion for pregnant women should be addressed more intensively at medical universities ( 66 ). Medical advice is an essential component of prenatal care, helping pregnant women to make informed decisions to protect both their health and the health of their unborn child.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, one of the reasons for the low involvement of antenatal physicians in the promotion of physical activity may be their insufficient education in this area during their studies and gynaecological specialization. Now that new, modern recommendations in this area have also been published in Poland ( 13 ), this important aspect of education and health promotion for pregnant women should be addressed more intensively at medical universities ( 66 ). Medical advice is an essential component of prenatal care, helping pregnant women to make informed decisions to protect both their health and the health of their unborn child.…”
Section: Discussionmentioning
confidence: 99%
“…A comparable study among American medical students showed they lacked knowledge of the specifics of exercise. [14] It demonstrates that it is essential to raise medical students' awareness and specific knowledge of the current physical activity recommendations to be better prepared to serve as future healthcare professionals. [15] The attitudes of medical students towards physical activity were found to be generally positive, with the majority acknowledging its importance in maintaining good health, preventing chronic diseases and improving well-being.…”
Section: Discussionmentioning
confidence: 99%
“…Physicians are often viewed as a person of authority on all things health-related, but receive very little-if any-training in exercise prescription and lack confidence in prescribing exercise for their patients. 21 We need to work on physicians and other primary care providers being comfortable prescribing and encouraging exercise for their patients. This starts with the healthcare provider asking the patient about their physical activity, which is why the Physical Activity as a Vital Sign initiative 22,23 is important to encouraging exercise for everyone.…”
Section: Considerations For Older Adultsmentioning
confidence: 99%